Chemical activation of nitrogen and sulfur co-doped graphene as defect-rich carbocatalyst for electrochemical water splitting - Li, Xintong; Duan, Xiaoguang; Han, Chen; Fan, Xiaobin; Li, Yang; Zhang, Fengbao; Zhang, Guoliang; Peng, Wenchao; Wang, Shaobin (Carbon (New York), 2019)
Heteroatom-doped carbonaceous materials are the most promising substitutes of noble metals as green catalysts for electrochemical water splitting. In this study, nitrogen and sulfur co-doped graphene (N,S-G) is synthesized via a one-pot calcination method. Subsequently, N,S-G is activated by ZnCl2 to enlarge the specific surface areas to construct a porous structure (a-N,S-G) The chemical activation can simultaneously regulate the elemental composition and porous structure of SNG toward enhanced carbocatalysis. As a result, in the OER process, the overpotential of a-N,S-G is only 330 mV vs. RHE at 10 mA cm−2 in 1 M KOH, which surpasses the most reported carbon catalysts. In the HER process, −10 mA cm−2 can be achieved at an overpotential of 0.29 V vs. RHE in 1 M KOH and 0.31 V vs. RHE in 0.5 M H2SO4. By combination with commercial carbon black (CB), the Tafel slopes of a-N,S-G@CB is lower than the metal-based catalysts. A new turnover frequencies (TOF) calculation method is involved to analyze the reactivity of specific active sites of carbocatalyst including both heteroatoms and structural defects. Therefore, the study provides an effective strategy for simultaneous modifications of surface chemistry and porous structure of graphene as high-performance and robust carbocatalysts toward electrochemical water splitting. [Display omitted]